EVALUATION OF PATIENTS WITH CONGENITAL LEFT VENTRICULAR OUTFLOW TRACT OBSTRUCTION - Gjurkova-Angelovska B; Kacarska R; Kuzevska-Maneva K; Jovanovska V; Neshkovska-Shumenkovska M; Nakeva-Janevska N (Medical Faculty, Ss. Cyril and Methodius University in Skopje, 2020)
Left ventricular outflow tract obstruction is a relatively common form of congenital heart disease accounting for 6%-10% of congenital heart defects and is a significant problem in pediatric cardiology. Obstruction may involve the arch of aorta, aortic valve and subaortic portion of the left ventriclе. The degree of stenosis and hemodynamic consequences may vary from hypoplastic left heart syndrome to almost normal hearts. The study included patients aged 0-14 years, examined at the University Clinic of Pediatric Diseases in Skopje during the period of March 2013 and March 2019. Echocardiography was the main diagnostic method applied. A total of 1100 examinations on selected patients were preformed in order to determine the timing for surgery. Some types of congenital left ventricular outflow tract obstruction were detected in 43 patients.
Евалуација на пациенти со вродени аномалии
Keywords: aortic stenosis; coarctation; congenital; obstruction